Dynamic Flux Balance Analysis in Cyanobacteria for Ethanol Production with Simultaneous Optimization Approaches - Delpino, Claudio (2014)
Fil: Delpino, Claudio. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química (PLAPIQUI), CONICET. Bahía Blanca, Argentina